2014
DOI: 10.2172/1204101
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of PV-smoothing controllers using distributed generators

Abstract: The power output variability of photovoltaic systems can affect local electrical grids in locations with high renewable energy penetrations or weak distribution or transmission systems. In those rare cases, quick controllable generators (e.g., energy storage systems) or loads can counteract the destabilizing effects by compensating for the power fluctuations. Previously, control algorithms for coordinated and uncoordinated operation of a small natural gas engine-generator (genset) and a battery for smoothing P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The aggregate capacity of the VPP is ∼1694 kW. Prior work demonstrated the control of the PNM BESS and the MdS BEMS to provide PV smoothing [57, 58] as well as the control of DETL assets [59].…”
Section: Vpp Assetsmentioning
confidence: 99%
“…The aggregate capacity of the VPP is ∼1694 kW. Prior work demonstrated the control of the PNM BESS and the MdS BEMS to provide PV smoothing [57, 58] as well as the control of DETL assets [59].…”
Section: Vpp Assetsmentioning
confidence: 99%
“…For instance, PNM research at the Prosperity Site has demonstrated PV smoothing 56 , load shifting 57 , and peak smoothing 58 . This team also conduced PV-smoothing control demonstrations using the prosperity battery and the MdS genset 59,60 .…”
Section: Vpp Designsmentioning
confidence: 99%
“…The remaining generators and demand response units at MdS, Prosperity and UNM would be controlled with a variety of communication protocols: -Control of the MdS devices will be conducted through a communication link to the Toshibadeveloped Building Energy Management System (BEMS). In a previous U.S.-Japan bilateral project, BEMS-connected DERs at MdS were controlled to provide PV smoothing using an OSIsoft PI historian 72 . -The prosperity battery is controlled using gain adjustments and auxiliary inputs in the control algorithm 73 , programmed into the Battery Energy Storage System (BESS) by Ecolt.…”
Section: Communicationsmentioning
confidence: 99%